Profit Efficiency and The Influence of Financial Performance Measures on Cost Efficiency of Rural Banks in Indonesia - Imansari, Arizka Rahmaninghadi; Saraswati, Erwin; Prihatiningtias, Yeney W. (Universitas Negeri Malang, 2023)
Efficiency for a bank is an important aspect to pay attention to realize a healthy and sustainable financial performance. This research aims to analyze the profit and cost efficiency of Rural Banks in Indonesia for the 2018-2022 period and examine the influence of financial performance measures on the cost efficiency of Rural Banks. The sample for this research was 497 BPRs in West Java, East Java, and Bali. Efficiency testing uses stochastic frontier analysis with an intermediation approach for cost efficiency and a production approach for profit efficiency. Financial performance measures represented by the NPL ratio, LDR, CAR, and total assets were tested using Tobit regression. The results of cost efficiency using the intermediation approach show that BPR in the three regions from 2019 to 2022 is in an inefficient condition. Similar to cost efficiency, the results of profit efficiency using a production approach show that BPRs from these three regions from 2019 to 2022 are in an inefficient condition. Based on the Tobit regression results, financial performance measures influence cost efficiency. Financial performance measures that influence cost efficiency are NPL, CAR, and total assets. The LDR ratio does not affect on cost efficiency.